Microbial gut evaluation in an angolan paediatric population with sickle cell disease - Delgadinho, Mariana (2022)
Sickle cell disease (SCD) is one of the most common genetic conditions worldwide. It can contribute up to 90% of under-5 mortality in sub-Saharan Africa. Clinical manifestations are very heterogeneous, and the intestinal microbiome appears to be crucial in the modulation of inflammation, cell adhesion and induction of aged neutrophils, the main interveners of recurrent vaso-occlusive crisis. Enterocyte injury, increased permeability, altered microbial composition and bacterial overgrowth have all been documented as microbial and pathophysiologic changes in the gut microbiome of SCD patients in recent studies. Our aim was to sequence the bacterial 16S rRNA gene in order to characterize the gut microbiome of Angolan children with SCA and healthy siblings as a control. A total of 72 stool samples were obtained from children between 3 and 14 years old. Our data showed that the two groups exhibit some notable differences in microbiota relative abundance at different classification levels. Children with SCA have a higher number of the phylum Actinobacteria. As for the genus level, Clostridium cluster XI bacteria was more prevalent in the SCA children, whereas the siblings had a higher abundance of Blautia, Aestuariispira, Campylobacter, Helicobacter, Polaribacter and Anaerorhabdus. In this study, we have presented the first microbiota analysis in an Angolan paediatric population with SCD and provided a detailed view of the microbial differences between patients and healthy controls. There is still much to learn before fully relying on the therapeutic approaches for gut modulation, which is why more research in this field is crucial to making this a reality.